Social norms as a barrier to women's employment in developing countries - Seema Jayachandran (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2019)
This paper discusses cultural barriers to women's participation and success in the labor market in developing countries. I begin by describing how gender norms influence the relationship between economic development and female employment, as well as how gender norms differ substantially across societies at the same level of economic development. I then discuss in more detail specific gender-related social norms and how they constrain women's employment. I present examples of policies aimed at dismantling these cultural barriers to female employment and the impacts they have.
Keywords: O1; J16; J22; Z1; 330; culture and institutions; developing countries; economic development; female employment; labor supply; social norms